Impact of postoperative intensity-modulated radiation therapy (IMRT) on the rate of bowel obstruction in gynecologic malignancy - Shih, Karin K.; Hajj, Carla; Kollmeier, Marisa; Frey, Melissa K.; Sonoda, Yukio; Abu-Rustum, Nadeem R.; Alektiar, Kaled M. (Gynecologic oncology, 2016)
The purpose was to determine the potential impact of IMRT on the rate of bowel obstruction (BO), in patients with gynecologic malignancies undergoing postoperative pelvic RT. We performed a retrospective review of all patients with endometrial or cervical cancer who received postoperative pelvic RT at our institution from 2000 to 2012. Patients who received definitive or palliative RT, or those with BO due to disease progression, were excluded. Standard two-sided statistical tests were used to evaluate for associated risk factors. Kaplan-Meier, Log rank and Cox proportional hazards regression analysis tests were performed for actuarial analysis. A total of 224 patients were identified, 120 (54%) received postoperative pelvic IMRT and 104 (46%) 3-dimentional (3-D) RT. Median follow-up time was 67months. BO was grade 1 (asymptomatic) in 2/228 (0.9%), grade 2 (conservative management) in 4 (1.8%), and grade 3≥ in 4 (1.8%). Overall, the 5-year actuarial rate of BO was 4.8%. The 5-year rate of BO in the IMRT group was 0.9% compared to 9.3% for 3-D RT (p=0.006). Patients with BMI≥30kg/m2 were less likely to develop BO (2.6% vs. 8.3; p=0.03). On multivariate analysis, only IMRT retained its significance as an independent predictor of less BO (p=0.022). The use of postoperative IMRT for cervical and endometrial cancer was associated with significant reduction in the rate of bowel obstruction. This difference maintained its statistical significance on multivariate analysis. Such finding if confirmed by others will help further solidify the benefit of IMRT in gynecologic cancers. •IMRT is associated with lower rate of bowel obstruction.•Lower bowel obstruction rate was independent of other prognostic factors.•Results of this study add further credence to the role of IMRT in gynecologic cancers.